THE HISTORY OF THE PARALYMPICS BOCCI IN BRAZIL AND ITS DEVELOPMENT AS A HIGH LEVEL SPORTS (Fiep Bulletin - online, 2013)
In Brazil the Paralympics “Bocci” was introduced in the year of 1995. This modality was shown by a team of Physical Educational Teachers from the National Association for Handicapped Sportspeople - NAHS – on the   I   Cerebral Palsy Paradsports Games made in Mar del Plata in Argentina. The modality is divided in four classes (BC1, BC2, BC3, and BC4). Bocci is an important sports activity for people with disability, in which we searched more knowledge about them while Paralympics' sports, besides improving the coordination and attention, according to the students' reports who played it as a relaxation, it is the opportunity of assuming important function in the society like as the sports. They start being recognized by what they really are regardless their disability. This work main reason was to research and show to our society the history and the beginning of the Paralympics emphasizing the adapted Bocci. It was made a Literature Review as a Scientific Research Method and through the enunciated evidences and answers, we intend to help enlarging the Adapted Bocci Game knowledge, and about the classified athlete in all categories through the adapted Physical Education. In terms of a high level of improvement Brazil has shown clear evolution in the BP International View, although there is a lot to be done while Public and Leisure Sport Politics related to this modality. These data show the investment relevance for the modality BP incentive in these regions, implying in the National Paradsports Management.
Keywords: Paralympics Bocci; Paradsports History; high level of improvement